2013
DOI: 10.1007/s11010-013-1694-7
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress leads to lipid accumulation through upregulation of SREBP-1c in normal hepatic and hepatoma cells

Abstract: Endoplasmic reticulum stress (ERS) has been found in non-alcoholic fatty liver disease. The study was to further explore the mechanistic relationship between ERS and lipid accumulation. To induce ERS, the hepatoblastoma cell line HepG2 and the normal human L02 cell line were exposed to Tg for 48 h. RT-PCR and Western blot were performed to evaluate glucose-regulated protein (GRP-78) expression as a marker of ERS. ER ultrastructure was assessed by electron microscopy. Triglyceride content was examined by Oil Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(57 citation statements)
references
References 28 publications
4
52
1
Order By: Relevance
“…Liver index and our histological data (H&E and oil red O staining) showed that ER stress induction by TM challenge leads to severe steatosis and hepatocytes ballooning. These results were consistent with several previously published studies (26,27); however, amygdalin administration before ER stress induction was unable to decrease lipid accumulation in the hepatic cells. Our pervious study reported that naltrexone attenuated ER stress induced liver steatosis (28).…”
Section: Effect Of Amygdalin On the Serum Lipids Levelssupporting
confidence: 94%
“…Liver index and our histological data (H&E and oil red O staining) showed that ER stress induction by TM challenge leads to severe steatosis and hepatocytes ballooning. These results were consistent with several previously published studies (26,27); however, amygdalin administration before ER stress induction was unable to decrease lipid accumulation in the hepatic cells. Our pervious study reported that naltrexone attenuated ER stress induced liver steatosis (28).…”
Section: Effect Of Amygdalin On the Serum Lipids Levelssupporting
confidence: 94%
“…Pharmacologically induced ER stress in HepG2 cells increased the expression of SREBP-1c via cap-independent internal translation of SREBP-1c mRNA by hnRNP-A1 (103,104), which in turn activated fatty acid synthesis in L02 cells (105). ER stress also induced hepatic steatosis via increased expression of hepatic VLDL receptor (VLDLR) through direct binding of the ATF4 transcription factor to the VLDLR promoter region leading to accumulation of TG (106).…”
Section: Er Stress and Lipotoxicity In Peripheral Organsmentioning
confidence: 99%
“…LXRs induce the expression of SREBP1c, a master regulator of lipid and cholesterol metabolism (51,54), and mediate lipid accumulation in hepatocytes, as can be observed by oil red O staining (55,56). Employing this methodology, we treated uninfected Huh7.5.1 and Huh7-25 cells with compounds and then stained them with oil red O to observe intracellular lipid accumulation.…”
Section: Molecular Interaction Of Neob With Lxrs Is Correlated With Tmentioning
confidence: 99%